Allium stent as a curative treatment for benign ureteral strictures: Preliminary experience, surgical technique, and functional results - Salciccia, Stefano; De Marco, Ferdinando; Sciarra, Alessandro; Moriconi, Martina; Alfarone, Andrea; Polese, Milena; Maggi, Martina; Del Giudice, Francesco; Gentilucci, Alessandro; De Berardinis, Ettore; Ricciuti, Gian Piero (Frontiers in Urology, 2022)
Objectives To evaluate the effectiveness and safety of the Allium™ ureteral stent as a curative treatment of benign ureteral strictures. Materials and methods We retrospectively reviewed the electronic database of the two centers of patients who underwent ureteral Allium™ positioning for different types of stenosis (benign or malignant). Between April 2017 and May 2021, 151 patients were treated with the Allium™ stent for ureteral strictures including benign and malignant stenosis. In total, 83 of them met the inclusion criteria for benign ureteral stricture and were included in final analysis. Results About the etiology of strictures, 79 (95.18%) were secondary to ureteroscopy or impacted stones and 4 (4.82%) were secondary to pelvic surgery. The median operating time was 47.9 ± 15.53 min, and the median length of strictures was 2.51 ± 0.84 (1-4) cm. The median time of follow-up was 18 months (range 1–48 months), the overall success rate was 85.5% (71/83), and no intraoperative or perioperative major complications were recorded. Among patients with failure (12 pts, 14.5%): 10 (83.33%) presented ureteral strictures again; among them, 8/10 were patients with a stricture length between 2 and 4 cm, 2 (16.67%) patients with pyelus–ureteral junction stenosis experienced the migration of the stent. All patients who experienced failure were treated surgically either with a robotic or laparoscopic approach. Conclusions In our preliminary experience, the Allium™ stent seems to be an effective and safe surgical treatment for benign ureteral stricture. Further analysis and prospective trials are necessary to better define the role of the Allium™ stent in the treatment of benign ureteral strictures.